2018
DOI: 10.1016/j.cej.2018.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor design for enzymatic hydrolysis of biomass under the biorefinery concept

Abstract: The dependence on non-renewable resources, particularly fossil fuels, has awaken a growing interest in research of sustainable alternative energy sources, such as bioethanol. The production of bioethanol from lignocellulosic materials comprises three main stages, starting with a pretreatment, followed by an enzymatic hydrolysis step where fermentable sugars are obtained for the final fermentation process. Enzymatic hydrolysis represents an essential step in the bioethanol production, however there are some lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(72 citation statements)
references
References 149 publications
(308 reference statements)
0
71
0
1
Order By: Relevance
“…However, during the EH, the presence of a wide range of compounds restrict the action of cellulase enzymes, including hemicellulose, phenolic compounds, acetyl groups and lignin, which act as physical barriers for the cellulases action. Also, lignin presence may cause cellulases deactivation, due to non-productive adsorption of the enzymes into lignin's surface (Pino et al, 2018). Moreover, it has been demonstrated that cellulases experience feedback inhibition by glucose and cellobiose (Andrić, Meyer, Jensen, & Dam-Johansen, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the EH, the presence of a wide range of compounds restrict the action of cellulase enzymes, including hemicellulose, phenolic compounds, acetyl groups and lignin, which act as physical barriers for the cellulases action. Also, lignin presence may cause cellulases deactivation, due to non-productive adsorption of the enzymes into lignin's surface (Pino et al, 2018). Moreover, it has been demonstrated that cellulases experience feedback inhibition by glucose and cellobiose (Andrić, Meyer, Jensen, & Dam-Johansen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1016/j.carbpol.2019.01.111 Received 14 December 2018 Received in revised form 29 January 2019; Accepted 31 January 2019 loadings (cellulose), a highly viscous slurry is formed, which reduces the mixing efficiency and affect the substrate (cellulose)-enzyme (cellulase) interaction (Andrić et al, 2010;Du et al, 2014). Therefore, different bioreactor design strategies have been development to overcome mass transfer limitations at high solid loadings (Pino et al, 2018). Horizontal bioreactors have been stated as a promising alternative to enhance high solid loading enzymatic hydrolysis (Dasari, Dunaway, & Berson, 2009;Du et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the high production cost of the enzymes, the low yields, and the considerable quantities of enzymes that are required during the process. For example, in the bioethanol production, the enzyme cost represents about 15-28% of the bioethanol selling price, or 20% of the overall bioethanol production costs [1]. Additionally, it has been reported that the biggest cost in the cellulase production is in the raw materials and consumables and that this cost varies according to the production approach, being the integrated method, where the cellulose is used as raw material to produce the cellulase, the most cost-effective compared to others that use glucose as raw material [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis consists of the degradation of polysaccharides in aqueous media that can be catalyzed by enzymes, acids, or bases to produce glucose [13,36,42,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. The hydrolysis result will depend on the reaction of enzymes and compounds [64][65][66][67].…”
Section: Hydrolysismentioning
confidence: 99%